The Effect Of Cashback And Free Shipping Programs On Consumer Buying Interest In The Gofood Application - Sri Winda Hardiyanti Damanik; Adelia Paramitasari; Muklis Setiawan (International Journal of Business and Quality Research, 2025)
The Influence of Cashback and Free Shipping Programs on Consumer Purchase Intention on the GoFood Application in North Cikarang. The background of this research is based on the increasingly tight competition among online food delivery services. Promotional programs in the form of cashback and free shipping are the main strategies used by GoFood to maintain consumer purchase interest. The research problem raised is the extent to which these two programs influence consumer purchase interest. Study ObjectivesThis aims to determine the impact of cashback and free shipping both partially and simultaneously on purchasing interest. This study uses a quantitative approach. with a causal associative approach. The research sample consisted of 100 GoFood user respondents in North Cikarang selected through a purposive sampling method. Data were analyzed using multiple linear regression after being collected through a questionnaire. The results of the study show that the cashback program has a positive effect on purchasing interest with a t-count value of 5.121> t-table 1.661, and the free shipping program also has an effect with a t-count value of 3.986> t-table 1.661. Both independent variables, namely cashback and free shipping, have a significance value of 0.000 <0.05 and an F-count value of 123.232> F-table 3.09, which means that both simultaneously influence the dependent variable, namely purchasing interest.